Thyroid Profile and Serum Lipid Level in Women with Normal Pregnancy - Kumar, Raj; Kumar, Sudeep; Arora, Manisha; Kumar, Dinesh; Sah, Sumesh Prasad; Sharma, Shivani (International Journal of Integrated Health Sciences, 2023)
Objective: To evaluate the changes in thyroid profile and serum lipid level in normal pregnancy.Methods: This observational study was conducted at the Department of Biochemistry of Santosh Medical College, Ghaziabad, UP, India, from June 2021 to February 2022. In this study, 200 average pregnant women were enrolled. The thyroid profile was estimated using the ELISA method, and the lipid profile was measured using the enzymatic kit method. All data were expressed as means and standard deviations, and SPSS version 17 was used for statistical analysis.Results: This observational study observed that the mean T3, T4, and TSH levels increased significantly in the second trimester compared to the first trimester. In contrast, the mean value of T3, T4, and TSH decreased in the third trimester as compared to the second trimester. The mean levels of total cholesterol, triglyceride, and LDL-cholesterol increased significantly, while the mean value of HDL-cholesterol decreased significantly in the second and third trimesters when compared to the first trimester.Conclusion: This study demonstrated abnormal lipid and thyroid metabolism. Changes in thyroid profile may be associated with adverse obstetric outcomes. The altered lipid parameters, mainly High TG and low HDL-C concentrations, may promote vascular dysfunction and oxidative stress.